2022
DOI: 10.1039/d1en01138c
|View full text |Cite
|
Sign up to set email alerts
|

Adding exogenous protein relieves the toxicity of nanoparticles to anammox granular sludge by adsorption and the formation of eco-coronas

Abstract: MgO nanoparticles (NPs) are widely used in bactericides, fuel cells and electronic materials and are frequently detected in aquatic environments. Anaerobic ammonium oxidation (anammox) is a highly efficient and economical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…During the incubation period, a greater number of BP aggregates were observed on the bottom of the EPEC incubation system compared to B. tropicus (Figure S10a). Previous studies have demonstrated adsorption of extracellular polymeric substances on the surface of nanoparticles, effectively altering aggregation processes in aqueous environments. , This process will prevent direct contact between the nanoparticles and cell membrane, thereby decreasing cytotoxicity . Given this, we hypothesize that BP nanosheets promoted protein production and secretion in EPEC, effectively mediating toxicity alleviation.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…During the incubation period, a greater number of BP aggregates were observed on the bottom of the EPEC incubation system compared to B. tropicus (Figure S10a). Previous studies have demonstrated adsorption of extracellular polymeric substances on the surface of nanoparticles, effectively altering aggregation processes in aqueous environments. , This process will prevent direct contact between the nanoparticles and cell membrane, thereby decreasing cytotoxicity . Given this, we hypothesize that BP nanosheets promoted protein production and secretion in EPEC, effectively mediating toxicity alleviation.…”
Section: Resultsmentioning
confidence: 82%
“…62,63 This process will prevent direct contact between the nanoparticles and cell membrane, 64 thereby decreasing cytotoxicity. 65 Given this, we hypothesize that BP nanosheets promoted protein production and secretion in EPEC, effectively mediating toxicity alleviation.…”
mentioning
confidence: 98%
“…Interestingly, natural organic matter was shown to have strong adsorption affinity to metal NPs, and the coating on the NP surface modulated eco-corona formation through ligand exchange and encapsulation mechanism attributed to surface functional groups. The biomolecules encapsulated on the surface of NPs also contributed to eco-corona formation through enhanced aggregation and negative charge properties while altering NP-induced biological processes . These findings implied that the role of eco-corona formation by proteins, lipids, and other natural metabolites in the bio–nano (or biomolecular–nano) system cannot be ignored.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The biomolecules encapsulated on the surface of NPs also contributed to eco-corona formation through enhanced aggregation and negative charge proper-ties 34 while altering NP-induced biological processes. 56 These findings implied that the role of eco-corona formation by proteins, 29 lipids, and other natural metabolites 57 in the bio− nano (or biomolecular−nano) system 58 cannot be ignored.…”
Section: Evolution Of the Active Interface Between Nps And Rootsmentioning
confidence: 99%
“…Commercial γ-Fe 2 O 3 NPs (99.5% purity, 20 nm) were purchased from Sinopharm, China. Briefly, the mixture of γ-Fe 2 O 3 NPs and sodium dodecylbenzenesulfonate with a ratio of 1:0.017 (w/w) was homogenized in an ultrasonic cell disruptor (Ningbo Scientz Biotechnology, China) at 40 kHz and 250 W. 15 The γ-Fe 2 O 3 NP suspension was prepared on a daily basis to avoid aggregation.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%